Oregano Essential Oil Interactions with Photogenerated Singlet Molecular Oxygen - Dimarco Palencia, Frida Claudia Daniela (2020)
Essential oils are a mixture of volatile compounds, products of the secondary metabolism of plants. Once extracted, they can be deteriorated losing their organoleptic and therapeutic properties due to various environmental factors, being light exposure in aerobic conditions the main cause. In this work, the oregano essential oil extraction and characterization from Origanum vulgare plants grown in the experimental field of the FTU-UNSL and its photodegradation in MeOH:H2O 60:40 v/v solvent were studied. Characterization by EIMS and NIST Mass Spectrometry indicates the main compounds of oregano essential oil, quantified in the extracted oil by GC-MS, are carvacrol (7.14%) and thymol (47.37%). Degradation of essential oil and its two major components can be caused by reactive oxygen species photogenerated from endogenous sensitizers as riboflavin. Our results suggest degradation occurs involving singlet molecular oxygen. Interaction of carvacrol and thymol with singlet oxygen is mainly a physical process, while essential oil has an important reactive component, which indicates there might be other constituents which could contribute to reactive photoprotection. The effect of simultaneous presence of oregano essential oil and tryptophan amino acid—used as a photooxidizable model under riboflavin-photosensitizing conditions—was studied in order to evaluate the possible photoprotection exerted by the essential oil.